Federalism and accountability with distorted election choices - Sebastian G. Kessing (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
This study analyzes the interaction between distorted election choices and the architecture of government with a focus on the implications for the accountability of politicians. Contrasting centralized with decentralized political systems, it is shown that centralization is likely to result in higher accountability if election choices are subject to small random distortions. Furthermore, equity and efficiency arguments for uniform policies in centralized systems are derived as these are likely to result in the better overall performance of politicians and in more equal performance across regions.
urn:nbn:de:101:1-201101244247
Keywords: H73; D72; 330; accountability; federalism; decentralization; retrospective voting; Föderalismus; Zentralstaat; Wiederwahl; Vergleich; Abstimmungsparadoxon; Theorie